Physical and psychosocial impact on children with cancer treatment: evaluating their quality of live - Andrade, Ana Carolina Machado de; Filipini, Rosangela; Liubartas, Natália; Coelho, Patricia Granja; Fonseca, Fernando Luiz Affonso (Revista da Faculdade de Ciências Médicas de Sorocaba, 2021)
Objective: To evaluate the life-quality and the physical/psychological/social impact on children and adolescents with ongoing cancer treatment. Methods: Quantitative, descriptive study with 35 children and adolescents with ages between 1.7 and 18 years, at the Pediatric Clinic of Hospital Estadual Mario Covas and the Oncology Outpatent Clinic of Faculdade de Medicina do ABC, Santo André, São Paulo. Data collection consisted in the application of a questionnaire to parents and children, with the instrument PedsQL™: Cancer Module Version 3.0 and PedsQL™: pediatric questionnaire about quality of life 4.0 Brazil. Data processed and analyzed by the Epi-info software, version 5.3.1. Results: Among 35 children, 60% were males, with mean age of 8.1 years and 12.3 months; leukemia cancer was diagnosed in 54,3% of the subjects. Pain was frequent in more than 50% of the cases and the aspects of their affected quality of life surpassed 40% according to patients and their parents/caregivers. Conclusions: Life-quality is altered by the implications that the diagnostic unleashed in their physical, social, and psychological development. The perception for those alterations, in most parents/caregivers, is similar to that of their children.